1998
DOI: 10.1002/(sici)1521-4095(199807)10:10<725::aid-adma725>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Electrode Materials for Rechargeable Lithium Batteries

Abstract: The performance and safety of rechargeable batteries depend strongly on the materials used. Lithium insertion materials suitable for negative and positive insertion electrodes are reviewed. Future trends, such as alternative materials for achieving higher specific charges—the Figure shows a scheme for reversible lithium storage in a high specific charge carbonaceous material—are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
1,951
5
27

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 2,845 publications
(2,055 citation statements)
references
References 208 publications
43
1,951
5
27
Order By: Relevance
“…Interestingly, the authors showed that most of the Li ions were inserted at potentials >0.5 V vs Li/Li + without any distinguishable plateau, similarly to the well-known "hard carbons". [ 30 ] However, the deinsertion took place at much higher voltages (with more than 80% of capacity delivered between 1 and 3.5 V vs Li/Li + ), resembling the behavior of H-rich carbons [ 30,31 ] (similarly to the previously described Figure 2 , profi le e). Furthermore the authors noticed that, upon manipulations (e.g., electrode manufacture), the layered structure of graphene tended to reassemble and restack, thus, unfavorably affecting the lithium-ion storage properties.…”
Section: Graphene As Li-ion Hostsupporting
confidence: 77%
“…Interestingly, the authors showed that most of the Li ions were inserted at potentials >0.5 V vs Li/Li + without any distinguishable plateau, similarly to the well-known "hard carbons". [ 30 ] However, the deinsertion took place at much higher voltages (with more than 80% of capacity delivered between 1 and 3.5 V vs Li/Li + ), resembling the behavior of H-rich carbons [ 30,31 ] (similarly to the previously described Figure 2 , profi le e). Furthermore the authors noticed that, upon manipulations (e.g., electrode manufacture), the layered structure of graphene tended to reassemble and restack, thus, unfavorably affecting the lithium-ion storage properties.…”
Section: Graphene As Li-ion Hostsupporting
confidence: 77%
“…vêm sendo extensivamente estudadas, com resultados superiores aos ânodos de grafite litiado, além da vantagem adicional de ausência da co-intercalação de solvente 21 . Entretanto, devido à menor capacidade de carga, e pior performance durante os ciclos de carregamento/descarregamento, esses materiais vêm sendo preteridos aos materiais carbonáceos anódicos 8 .…”
Section: Baterias Secundárias De Lítiounclassified
“…Assim, não surpreendentemente, entre os mais estudados dispositivos secundários de alta densidade de energia estão os que utilizam o lítio. Aspectos científicos relacionados aos eletrodos utilizados em baterias secundárias de lítio foram recentemente discutidos em uma extensa revisão 8 .…”
Section: Introductionunclassified
See 2 more Smart Citations